Detection of Uterine Cavity Pathology in Subfertile Women Prior to In Vitro Fertilization Using Transvaginal Sonography and Office Hysteroscopy - Lusiana, Nadya; Werdhani, Retno Asti; Maidarti, Mila; Harzif, Achmad Kemal; Sumapraja, Kanadi; Yanfaunnas, Atika Mahira; Ampri, Irfan Arieqal Hatta; Talya, Natasha; Pratama, Gita (Indonesian Journal of Obstetrics and Gynecology, 2026)
Objective: To compare transvaginal sonography (TVS) and office hysteroscopy in detecting uterine cavity pathology in subfertile women prior to in vitro fertilization (IVF).Methods: This retrospective cross-sectional study included 104 subfertile women who underwent both TVS and office hysteroscopy at the Yasmin IVF Clinic, Dr. Cipto Mangunkusumo Kencana Hospital, Jakarta. Findings from TVS and hysteroscopy were compared with histopathological results for chronic endometritis, endometrial polyps, submucosal fibroids, and endometrial hyperplasia. Findings of uterine septum and intrauterine synechiae on TVS were compared with hysteroscopy as the reference standard. Results: Office hysteroscopy detected chronic endometritis in 16.3% of subjects, with a sensitivity of 33% and specificity of 68%, whereas TVS did not identify any cases. Submucosal fibroids were detected by both modalities with identical specificity (100%) and sensitivity (75%). Endometrial polyps were identified in 47.1% of cases by hysteroscopy and 15.4% by TVS. TVS demonstrated higher specificity (88% vs. 35%), although both modalities showed low sensitivity (15% for TVS vs. 50% for hysteroscopy). Both methods accurately detected endometrial hyperplasia, showing high specificity (97%). Uterine septum and intrauterine synechiae were detected exclusively by hysteroscopy. Conclusion: Both TVS and office hysteroscopy are effective in detecting submucosal fibroids and endometrial hyperplasia. However, only hysteroscopy can identify chronic endometritis, uterine septum, and intrauterine synechiae, while TVS demonstrates higher specificity for detecting endometrial polyps. Histopathology remains the gold standard, and office hysteroscopy provides important complementary diagnostic value prior to IVF. Keywords: in vitro fertilization, office hysteroscopy, sub-fertility, transvaginal sonography